The Coupled Dynamic and Thermodynamic Processes for Secondary Eyewall Formation. Issue 17 (9th September 2018) - Wang, Xingbao; Li, Qinglan; Davidson, Noel E.
Abstract: Using a previously documented successful simulation of secondary eyewall formation (SEF), the coupled dynamic and thermodynamic processes during SEF are investigated from an axisymmetric mean perspective. The budgets of momentum, density potential temperature, and radial pressure gradient force (PGF) with very small residuals reveal that rather than a single process dominating, the SEF is the consequence of tight coupling processes between the hurricane tangential wind, transverse circulation, diabatic heating, mean and eddy fluxes of momentum and heat, and the hurricane boundary layer. The collective actions of these coupling processes generate the following conditions for the SEF: (i) along with slow eyewall contraction, the azimuthal‐mean tangential wind increases on the inner side of the eyewall; (ii) while the regions in the eye and beyond the eyewall are warming, a lesser warming or cooling zone sandwiched between these two warming regions appears near the axis of maximum vertical velocity; (iii) low‐level pressure decreases (increases) with the column‐integrated warming (cooling); the increment in the PGF beyond the eyewall brings about a significant low‐level radial and tangential wind increment at SEF radii, and (iv) the hurricane boundary layer radial flow corresponding to the PGF increment enhances the convergence of moisture and angular momentum within the SEF radii. Eventually, these processes result in the SEF. Key Points: Prior to secondary eyewall formation, a column‐integrated heating zone appears over secondary eyewall formation radii Significant increases in low‐level pressure gradient and radial and tangential winds occur near the column warming zone The enhanced convergence of moisture and angular momentum at secondary eyewall formation radii leads to secondary eyewall formation